Metabolomic profiling of ten cacao genotypes from Antioquia, Colombia reveals local effects on nutritional composition - Galeano, E.; Lopez, J.M.; Agudelo, C.; Osorio, E.; Maruenda, H. (Academic Press, 2025)
Theobroma cacao beans exhibit considerable genetic and geographic diversity, which significantly influences their chemical composition. These variations affect the nutritional, health-promoting, and organoleptic qualities of cacao products. This study aimed to characterize the metabolic profiles of ten cacao genotypes cultivated in two distinct regions of Antioquia, Colombia, using proton nuclear magnetic resonance (¹H NMR) spectroscopy, and to evaluate the impact of geographic origin on key metabolites related to cacao quality. Twenty-one bioactive metabolites, including amino acids, sugars, and secondary metabolites, were identified and quantified in cacao beans from the Urabá and Northeast regions. Multivariate statistical analyses were employed to discern metabolic patterns associated with genotype and cultivation sites. Significant differences in metabolite concentrations were observed between the regions. Beans from Urabá displayed higher levels of amino acids, xanthine derivatives, and antioxidant compounds such as theobromine and epicatechin. Genotypes TSH565, FEAR5, ICS1, and CCN51 showed superior metabolic profiles in Urabá, while FSV41 was notable in the Northeast. Multivariate analyses revealed distinct clustering by geographic origin, highlighting the influence of environmental factors on metabolite expression. The stable, warm, and humid climate of Urabá appears to promote the accumulation of metabolites linked to enhanced protein quality, energy metabolism, and health benefits.
Keywords: Theobroma cacao; Metabolomics; Geographic variation; Genetic diversity; Proton NMR spectroscopy; Bioactive metabolites; Antioquia; https://purl.org/pe-repo/ocde/ford#1.06.05